(untitled) (World Bulletin of Education and Learning, 2026)
The article analyzes key aspects of the history of Uzbek national dance and the activities of Mukarrama Turgʻunboyeva. The author examines in detail M. Turgunboyeva’s contribution to preserving national dance traditions, elevating them to the level of stage art, creating new stage compositions, establishing a professional dance school, and promoting Uzbek dance art internationally. The article also evaluates the artistic, aesthetic, and pedagogical significance of Turgunboyeva’s work for the development of national choreography.